1994
DOI: 10.1159/000110357
|View full text |Cite
|
Sign up to set email alerts
|

Justification of Hospital Days and Epidemiology of Discharge Delays in a Department of Neurology

Abstract: We have developed a protocol to identify unnecessary days of hospitalisation in the Department of Neurology of the Centre Hospitalier Universitaire Vaudois, Lausanne, Switzerland. Seventy-four parameters (medical, social, type of investigation and treatment, degree of disability and of dependence) potentially associated with the length of stay were studied prospectively in 511 nonselected patients consecutively admitted to the Department over a period of 5 months. Each day spent on the wards was analyzed on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…[8][9][10][11][12][13][14] Furthermore, patterns in the ordering of medical tests and factors that determine the use of investigations have also been described in countries outside 15 This amounts to a 2.5% increase overall, but the figure for general internal medicine (including elderly care medicine) was 6.6%. This is of concern since inpatient beds are a costly resource, which is ever more precious as demands on the NHS grow through an increasing number of annual hospital admissions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13][14] Furthermore, patterns in the ordering of medical tests and factors that determine the use of investigations have also been described in countries outside 15 This amounts to a 2.5% increase overall, but the figure for general internal medicine (including elderly care medicine) was 6.6%. This is of concern since inpatient beds are a costly resource, which is ever more precious as demands on the NHS grow through an increasing number of annual hospital admissions.…”
Section: Discussionmentioning
confidence: 99%
“…15 Identified factors predicting prolonged LOS in other countries include specialty of attending physician, nosocomial infection, and delay in obtaining laboratory or radiological examination results. [8][9][10][11][12] Among the elderly, diagnoses of fall, dementia, fracture, neoplasm, bronchitis, arterial disease, and hyponatraemia are known to be associated with longer LOS. 13 14 The single most useful patient characteristic for predicting LOS, in our data, was patient age; presumably this reflects a greater need for pre-discharge social care planning in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…In one UK study, it was revealed that 88% of adult patients with a delayed discharge had a primary neurological diagnosis [ 18 ]. Awaiting provision of social care, home adaptations and transfer to another care facility are all associated with an inappropriate LoS amongst this patient population [ 18 , 23 - 25 ]. Similarly, a study of patients with brain injury revealed that failure to find a suitable placement and failure to obtain funding for post discharge support were common causes of delayed discharges [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most delays among hospitalized patients stem from scheduling of diagnostic test procedures [1,2]. The types of events that delay patient management relate to a large variety of medical, organizational, administrative and technical obstacles that often render a timely and expeditious management difficult.…”
Section: Introductionmentioning
confidence: 99%